Social Identity Crisis in India: A Comparative Analysis of BJP Administrations - Mansoor, Safia; Khalid, Iram; Mukhtar, Asia (Annals of Human and Social Sciences, 2022)
This research examines the Hindutva synonymous with the Hindu nationalism, discusses its various aspects and explains its mainstreaming under the BJP or Bharatiya Janata Party-led Hindu nationalist governments through the lens of Social Identity theory. The paper aims at addressing the social identity crisis in modern Indian society, given the prevalence of Hindutva under the auspices of BJP. Additionally, it holistically highlights the role of the Vajpayee and Modi governments in propagating Hindutva in social, legal, and political domain, as well as creating the ‘Otherisation’ rhetoric. The research is significant as it develops a nexus between the social aspects of group identity and the politics, in order to develop a conceptual discourse on the Hindutva in building up Hindu identity and mobilizing masses in political realm. Theoretical framework employed is Social Identity theory in order to assess the vital role of social identity in Indian polity. The methodology used is qualitative method and the type of social research is comparative analysis. This research endeavor concludes that ‘Hindutva under BJP administrations has generated polarization process in the society which has dual ramifications: prevailing ‘national identity crisis, with assertive ‘Hindu identity’ on one side and accumulated Indian identity on other, coupled with hovering religious extremism across the country.